Why We Sing: Music, Word, and Liturgy in Early Christianity : Essays in Honour of Anders Ekenberg's 75th Birthday - Berglund, Carl Johan,; Kelhoffer, James A.,; Crostini, Barbara, (Vigiliae Christianae, Supplements ;, 2022)
This volume sheds new light on an array of late ancient Christian liturgical sources, practices, and traditions emerges from these multidisciplinary studies on the interplay of New Testament writings, ancient music, liturgical spaces, biblical interpretation, and reception history.